Improvement of Corrosion Resistance of Rare Earth Element (REE)-Based Anodic Oxidation Coating on AZ91D Magnesium Alloy - Mohd Zamzuri, Mohammad Zain; Suhaimi, Illias; Mokhtar, Mat Salleh; Khairul Azwan, Ismail; Nooraizedfiza, Zainon (Scientific.net, 2013)
Link to publisher’s homepage at http://www.scientific.net/AMM/details